Perancangan Sistem Identifikasi Dengue Hemorrhagic Fever (DHF) Berbasis Rekam Medis Elektronik untuk Menunjang Pelaporan Kejadian Luar Biasa - Vahreza, Phahira Han; Setyawan, Adhita Arif; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Advances in technology that are increasingly developing can be a benefit for hospitals to support the effectiveness of officer performance. Methods for collecting research data used include literature studies, interviews, and observations with descriptive analysis. System developmenlt using the agile method. The reporting is made into an application that uses visual programming and a Microsoft Access database. The resultsl of thel information systeml design carried out using the selectedl method can increase the efficiency of reporting carried out by medicall record officers to produce accurate data to be sent to the Health Office.In addition, this information is able to maximize services for patients and the quality of service in the hospital can increase. Studies conducted at Hospital X Bandung City, one of which is in the medical recordsinstallation for Dengue Hemorrhagic Fever (DHF) reports that have not been computerized, show that technology improves the performance of hospital staff. There are several problems in the medical record installation, namely the delay in the process of making reports that still use a paper-based manual system (paperbase). By evaluating the information system electronically, it can help medical record officers makeDengue Hemorrhagic Fever (DHF) reports quickly, accurately, and completely.